The Tradition of al-Qira’at and the Role of Qurra’: From Historical Codification to Its Application in Contemporary Islamic Education - Muhammad Said; Ahmad Abdullah Faqih; Muhammad Shohib (Ambarsa : Jurnal Pendidikan Islam, 2026)
Al-Qira’at is one of the key branches of Islamic knowledge that plays an essential role in comprehensively understanding the Qur'an. This study aims to historically examine the development of al-Qira’at or reading style and the role of Qurra’ who have been central figures in the transmission of the Qur'anic recitations. Employing a qualitative approach with a historical and descriptive-analytical methodology, this research analyzes both classical and contemporary literature on the science system of reading style. Unlike previous studies that primarily focused on the technical aspects of recitation, this research integrates historical, methodological, and educational dimensions, particularly in relation to contemporary Islamic education. The findings show that it began during the time of the Prophet Muhammad (PBUH) through the concept of the seven ahruf, and was subsequently codified by the prominent Reciters imams under strict standards that include three criteria: alignment with the Uthmanic script, conformity with Arabic linguistic rules, and an authentic chain of transmission. The seven main imams of Reading style—Nafi', Ibn Kathir, Abu 'Amr, Ibn 'Amir, 'Ashim, Hamzah, and Al-Kisai—established a robust transmission tradition that persists to this day. This research underscores the significance of it not merely as a technical matter of recitation but as an intellectual heritage that must be preserved and developed within the framework of modern Islamic education, especially through its integration into the curricula of Islamic boarding school and Islamic universities. The significance of this research lies in its ability to bridge the historical depth of it with its practical application in contemporary Islamic pedagogical practices.